Lipid Droplets in Neurodegenerative Disorders - Farmer, Brandon C.; Walsh, Adeline E.; Kluemper, Jude C.; Johnson, Lance A. (Frontiers in Neuroscience, 2020)
Knowledge of lipid droplets (LDs) has evolved from simple depots of lipid storage to dynamic and functionally active organelles involved in a variety of cellular functions. Studies have now informed significant roles for LDs in cellular signaling, metabolic disease, and inflammation. While lipid droplet biology has been well explored in peripheral organs such as the liver and heart, LDs within the brain are relatively understudied. The presence and function of these dynamic organelles in the central nervous system has recently gained attention, especially in the context of neurodegeneration. In this review, we summarize the current understanding of LDs within the brain, with an emphasis on their relevance in neurodegenerative diseases.